Disentangling the Impacts of Anthropogenic Aerosols on Terrestrial Carbon Cycle During 1850–2014. Issue 7 (9th July 2021) - Zhang, Yuan; Ciais, Philippe; Boucher, Olivier; Maignan, Fabienne; Bastos, Ana; Goll, Daniel; Lurton, Thibaut; Viovy, Nicolas; Bellouin, Nicolas; Li, Laurent
Abstract: Aerosols have a dimming and cooling effect and change hydrological regimes, thus affecting carbon fluxes, which are sensitive to climate. Aerosols also scatter sunlight, which increases the fraction of diffuse radiation, increasing photosynthesis. There remains no clear conclusion whether the impact of aerosols on land carbon fluxes is larger through diffuse radiation change than through changes in other climate variables. In this study, we quantified the overall physical impacts of anthropogenic aerosols on land C fluxes and explored the contribution from each factor using a set of factorial simulations driven by climate and aerosol data from the IPSL‐CM6A‐LR experiments during 1850–2014. A newly developed land surface model which distinguishes diffuse and direct radiation in canopy radiation transmission, ORCHIDEE_DF, was used. Specifically, a subgrid scheme was developed to distinguish the cloudy and clear sky conditions. We found that anthropogenic aerosol emissions since 1850 cumulatively enhanced the land C sink by 22.6 PgC. Seventy‐eight percent of this C sink enhancement is contributed by aerosol‐induced increase in the diffuse radiation fraction, much larger than the effect of the aerosol‐induced dimming. The cooling of anthropogenic aerosols has different impacts in different latitudes but overall increases the global land C sink. The dominant role of diffuse radiation changes found in this study implies that future aerosol emissions may have a much stronger impacts on the C cycle through changing radiation quality than through changing climate alone. Earth system models need to consider the diffuse radiation fertilization effect to better evaluate the impacts of climate change mitigation scenarios. Plain Language Summary: The aerosols emitted by human activities can change climate and increase diffuse fraction of sunlight. All these changes can influence the carbon fixation of vegetation on land, further affect the atmospheric CO2 concentration and the climate. Currently, there is still no agreement on whether climate or diffuse light change is more important in affecting land carbon fixation. To solve this problem, we designed a set of experiments and used a newly developed computer code to investigate the impact of anthropogenic aerosols on land carbon sink from each climate factor and diffuse light. We found that since 1850, human‐caused aerosol emissions increased the land carbon sink by about 2 years of present‐day anthropogenic CO2 emissions. Seventy‐eight percent of this large increase in carbon sink is mainly contributed by the increase in diffuse light fraction. The cooling caused by aerosols affected the land carbon sink differently in different latitudes and overall increased the global land carbon sink. The important role of diffuse light found here implies that aerosols emissions may have stronger impacts through changing radiation quality than through changing climate alone in the future, and climate computer codes need to consider diffuse light to better evaluate the impacts of climate change mitigation policies. Key Points: A set of factorial simulations are set up to investigate the anthropogenic aerosol impacts on land C fluxes during 1850–2014 Anthropogenic aerosols cumulatively enhanced land C sink by 22.6 PgC since 1850 The large C sink increase is mainly attributed to aerosol‐induced diffuse radiation changes, followed by the cooling effect